Estimating the incomes of people who depend on forests - Wollenberg, Eva Karoline; Nawir, A.A. (1998)
Estimating the incomes of people whose livelihoods depend on the forests is a key to understanding their well being and the use of the forest. Yet there has been little agreement about the methods to undertake such assessment. This paper reviews the strengths and weaknesses of the methods available. The authors summarise the methodologies used in 10 case studies and use these cases, as well a insights from their own research in Indonesia, to suggest ways of overcoming the logistics of collecting income information related to possibly hundreds of products. Attention is also drawn to the difficulties of assigning values to forest products where such products are not sold. This review indicates some of the reasons why good information remains unavailable: expense of collecting information, weak application of methods and incomparable data. Also, some basic economic concepts do not fit very well the values, perceptions or conditions of forest dwellers. One conclusion is that the methods currently in use for accurately estimating incomes are costly and probably not possible or appropriate for many development efforts, especially where long-term monitoring is required.